2009
DOI: 10.1111/j.1464-410x.2008.08263.x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid tumour ‘oncocytoma‐chromophobe renal cell carcinoma’ of the kidney: a report of seven sporadic cases

Abstract: OBJECTIVES To determine whether renal hybrid tumours (HT) appear as a specific clinical and radiological entity, as HT are characterized by the association of both oncocytes and chromophobe cells within the same tumour, and have been described in patients with oncocytosis and Birt‐Hogg‐Dube syndrome. PATIENTS AND METHODS We reviewed the medical charts of 67 patients who had a partial or radical nephrectomy in our institution for renal oncocytoma (RO, 24), chromophobe renal cell carcinoma (CRCC, 36) and HT (sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…Alternatively, these oncocytomas may represent hybrid tumors. 22,23 It is intriguing that the distal tubule-specific protein FXYD2 is preferentially expressed in chromophobe RCC when both chromophobe RCC and oncocytoma are thought to derive from the distal nephron. Previous investigations using mRNAexpression analysis demonstrated that chromophobe RCC shows increased expression of distal nephron genes when compared with oncocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these oncocytomas may represent hybrid tumors. 22,23 It is intriguing that the distal tubule-specific protein FXYD2 is preferentially expressed in chromophobe RCC when both chromophobe RCC and oncocytoma are thought to derive from the distal nephron. Previous investigations using mRNAexpression analysis demonstrated that chromophobe RCC shows increased expression of distal nephron genes when compared with oncocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional (and pure) clear cell carcinomas, oncocytomas, chromophobe renal cell carcinomas, and papillary renal cell carcinomas have also been reported in the setting of BHD [9,10]. Recently, three small series of sporadic HOCT have been published [11][12][13], but without any chromosomal or molecular genetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published series of sporadic HOCT [11][12][13], no data on numerical chromosomal anomalies have been provided. Our series showed multiple numerical chromosomal aberrations, both monosomic and polysomic.…”
Section: Discussionmentioning
confidence: 99%
“…RO and chRCC are often considered to be extremities of the same morphological spectrum (Delongchamps et al 2009). Proper differentiation largely relies on haematoxylin and eosin (H&E) histochemistry of sections, and an experienced histopathologist to discern the characteristic histomorphologic features that separate the two entities.…”
Section: General Introductionmentioning
confidence: 99%
“…Due to considerable morphological and histological overlap between the two entities, they are often considered to be extremes of the same morphological spectrum (Delongchamps et al 2009). Accurate differentiation between benign RO and malignant chRCC will obviously lead to better patient management and follow-up strategies in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%